CONTENT ANALYSIS: A COMPARATIVE STUDY OF DIFFERENT GENRES OF PAKISTANI PODCASTS - Hassam UL Haq; Anum Shahid; Fahad Abdullah; Iram Sagheer; Sabrina A Rasool (PAKISTAN ISLAMICUS (An International Journal of Islamic & Social Sciences), 2024)
This study analyses the different genres of podcasts listened to and watched in Pakistan. The world of podcasts enables content producers to share what they have created and, through on-demand listening, could encourage vibrant communities. They still have an impact on stories and contemporary communication. Researchers are here tending to compare eight different genres of podcasts, i.e., comedy, music, sports, religion, technology, education, news, politics, and economy, with further different features of genre, i.e., language and tone, entertainment and fun, content focus, target audience and guest and host. Delving into the characteristics of each genre, including language and tone, entertainment and fun, content focus, target audience, and guest-host dynamics, this research aims to provide a comprehensive understanding of the podcasting landscape. The technique that was used to gather the data involved listening to the podcast carefully, observing the characteristics of that genre, and then taking notes. This research employed both qualitative and quantitative analysis, implementing purposeful sampling to ensure a diverse representation of podcasts in Pakistan. Each podcast, with a duration of approximately 30 to 40 minutes, underwent content analysis. Within the article, the researchers have visually represented the viewership percentages of various podcast genres in Pakistan through an informative graph and explained how language and culture enhance the podcasting environment.